Endogenous Monetary Policy Credibility in a Small Macro Model of Israel - Argov, Eyal.; Epstein, Natan; Karam, Philippe; Rose, David (Washington, D.C. : International Monetary Fund, 2007)
This paper extends a small linear model of the Israeli economy to allow for nonlinearities in the inflation-output process that arise from convexity in the Phillips curve and endogenous monetary policy credibility. We find that the dynamic responses to shocks in the extended model more closely resemble features in the data from the period 2001?03. In particular, the extended model does a much better job in accounting for the deterioration in monetary policy credibility and the output costs of regaining monetary policy credibility once it has been lost.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet